Inclusion indicators and institutional policies in a brazilian Public University - Louzada, Juliana Cavalcante de Andrade; Martins, Sandra Eli Sartoreto de Oliveira (Debates em Educação, 2024)
The assessment of inclusive institutional policies in Higher Education is a current discussion in Brazil. However, indicators of institutional policies dedicated to this issue are rarely considered as investigated criteria within the scope of institutional administrative management at this level of education. Thus, we sought to investigate how the results of the evaluation carried out by the academic community (students, professors, and staff) combined with dialogue with management can contribute to a university with inclusive educational principles. The Higher Education Inclusion Index was applied in a virtual format and the data were analyzed in using a traffic light system and descriptive analysis. The results suggest the need for strategies to disseminate inclusive policies and actions so that the academic community recognizes and accesses the different services offered to meet their demands. In this sense, the INES has been considered an important tool that enables the evaluation of institutional aspects of inclusion in the university and should be widely used to ensure inclusion, equity, and social justice in the university. In addition, dialogue with management facilitates the understanding of the results and suggests actions to make the university increasingly inclusive.